PENERAPAN METODE PEMBELAJARAN BRAINSTORMING (CURAH PENDAPAT) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS DAN PRESTASI BELAJAR - Ani Nopiarni (DIADIK, 2022)
This study aims to describe the application of the brainstorming learning method to improve students’ logical thinking skills and learning achievement in Indonesian language subjects in class XI IPA I SMA N I Pajar Bulan, Lahat Regency. The research design used is classroom action research and quasi-experimental research. The research subjects were students of class XI IPA I SMA N I Pajar Bulan in the odd semester of the 2020/2021 school year. The quasi-experimental samples are class XI IPA 2 and class XI IPA 3 at SMA N I Pajar Bulan. This research instrument uses observation sheets and tests. Research data were analyzed by descriptive statistics, average (mean), percentage, and t-test. The results showed that the application of the brainstorming learning method could improve logical thinking and student achievement in class XI IPA I at SMA N I Pajar Bulan, Lahat Regency.